Brand Equity in Good and Bad Times: What Distinguishes Winners from Losers in Consumer Packaged Goods Industries? - Rajavi, Koushyar; Kushwaha, Tarun; Steenkamp, Jan-Benedict E.M. (Journal of Marketing, 2023)
This article examines why some brands are able to ride the wave of macroeconomic expansions, whereas other brands are better able to successfully weather contractions. Using a utility-based framework, the authors develop hypotheses on how the impact of these shocks on brand equity is moderated by six strategic brand factors: price positioning, advertising spending, product line length, distribution breadth, brand architecture, and market position. The authors utilize monthly data on 325 national consumer packaged goods brands in 35 categories across 17 years from the United Kingdom to obtain quarterly sales-based brand equity estimates. The two preeminent brand factors are distribution and assortment. Distribution is by far the most important factor in contractions. It is also the most important factor in expansions. In short, in good times and bad times, extensively distributed brands win. A wide assortment is also a strong contributor to brand equity in expansions, while it does not destroy brand equity in contractions. The authors further find that advertising spending, premium price positioning, umbrella branding structure, and market leadership matter in expansions and/or contractions, and the magnitude of their effects on brand equity is relatively modest. The discussion concludes with managerial implications.